1999
DOI: 10.4269/ajtmh.1999.60.54
|View full text |Cite
|
Sign up to set email alerts
|

Short report epidemiologic studies on cutaneous leishmaniasis in eastern Panama.

Abstract: Abstract. The Panamanian Ministry of Health, through the Interamerican Development Bank, contracted the Gorgas Memorial Laboratory to conduct epidemiologic studies on leishmaniasis and malaria in eastern Panama from July 1984 through June 1985. Preliminary results of the biomedical and entomologic teams investigating the epidemiology of cutaneous leishmaniasis in the eastern part of the country are presented in this short report. The principal findings of the study revealed 1) a large disparity in the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…9 Although human samples from all the endemic regions of the country were analyzed, there is an underrepresentation in our sample of some endemic areas, particularly from remote zones located near neighboring countries where other Leishmania species have been reported. Therefore, based on previous reports, [9][10][11][12] we cannot exclude the current presence in the country of other human Leishmania species. In this regard, studies in particular endemic areas such as the Darien province near the Colombian border are necessary to confirm the taxonomy of Leishmania parasites that infect humans in these communities.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…9 Although human samples from all the endemic regions of the country were analyzed, there is an underrepresentation in our sample of some endemic areas, particularly from remote zones located near neighboring countries where other Leishmania species have been reported. Therefore, based on previous reports, [9][10][11][12] we cannot exclude the current presence in the country of other human Leishmania species. In this regard, studies in particular endemic areas such as the Darien province near the Colombian border are necessary to confirm the taxonomy of Leishmania parasites that infect humans in these communities.…”
Section: Discussionmentioning
confidence: 97%
“…Lutzomyia species implicated in the transmission of L. mexicana and L. amazonensis were not identified in this study, although sporadic human cases caused by these species have been reported in the country. [9][10][11][12] The natural vector of AVL, Lu. longipalpis , was not captured.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations